Analisis Distribusi Titik Parkir di Jalur Jalan Utama Kota Makassar - Qaiyimah, Dinil (UNIVERSITAS NEGERI MAKASSAR, 2020)
The purpose of this study was to determine the distribution of parking lots in Makassar City both officially and unofficially managed.. The study was conducted directly in the field by plotting the parking spot and interviews with related parties in the field. Mapping was done using ArcGIS 10.1 software. Mapping aims to identify the distribution of parking points in Makassar City, both managed officially and unofficially. The results showed that the official parking area spread on Jl. Pengayoman, Jl. Dr. Sam Ratulangi, Jl. Southern Veterans, Jl. Perintis Kemerdekaan, Jl. Cendrawasih, Jl. Letjen Hertasning, Jl. Sultan Alauddin, Jl. Rappocini Raya, Jl. Boulevard Raya, Jl. Urip Sumiharjo, Jl. AP. Pettarani, Jl. Bandang, Jl. Cakalang, Jl. Landak Baru, Jl. General Sudirman, Jl. Ahmad Yani, Jl. HOS Cokroaminoto and Jl. Saddang River. The officially parked parking area of 78 parking lots and 104 parking lots are unofficially managed and the number of official parking attendants is 104 persons and the unofficial parking officer is 203 persons.